2021
DOI: 10.1177/21582440211021823
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Leadership and Knowledge Sharing: The Effects of Positive Reciprocity and Moral Efficacy

Abstract: Despite the pivotal function of knowledge sharing for enterprises in today’s highly competitive and ever-changing economic environment, the mechanism about how ethical leadership impacts employees’ knowledge sharing remains a largely unexplored domain in the literature. Drawing on the social exchange theory and social learning theory, this study examines how ethical leadership helps to encourage followers’ knowledge sharing behavior considering the dual-mediating effects of positive reciprocity and moral effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 42 publications
1
23
0
1
Order By: Relevance
“…First, the results of this study have shown that ethical leadership is positively related to employee knowledge sharing. This is consistent with previous studies (e.g., Lei et al, 2019 ; Su et al, 2021 ). Current studies have fully demonstrated the importance of ethical leadership in promoting employee knowledge sharing.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…First, the results of this study have shown that ethical leadership is positively related to employee knowledge sharing. This is consistent with previous studies (e.g., Lei et al, 2019 ; Su et al, 2021 ). Current studies have fully demonstrated the importance of ethical leadership in promoting employee knowledge sharing.…”
Section: Discussionsupporting
confidence: 94%
“…Second, previous studies have found many mediators between ethical leadership and knowledge sharing, such as employees’ subjective well-being, social media interaction, positive reciprocity, moral efficacy, controlled motivation, moral identity, relational social capital etc. ( Bavik et al, 2018 ; Abdullah et al, 2019 ; Bhatti et al, 2020 ; Su et al, 2021 ). This study further to prove that employees’ identifications are also important mediators.…”
Section: Discussionmentioning
confidence: 99%
“…Leader support is critical for fostering a culture of knowledge sharing among company workers ( Tang et al, 2015 ). EL is considered an effective leadership style ( Bedi and Wordley, 2019 ), and is linked to KS behaviors ( Su et al, 2021 ). As part of knowledge management, the goal is to establish an environment that encourages individuals to share information and build a shared understanding of the company’s mission.…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…Organizational effectiveness and success are directly linked to EL and knowledge sharing (KS) connection and also linked to leaders’ ability to advise, organize, motivate, and empower their followers ( Le and Lei, 2018 ). Most studies on leadership focus on how leaders influence their subordinates, rather than how their subordinates get advantage from their leadership guidance and supervision ( Su et al, 2021 ). There is a dire need to find that how knowledge sharing behavior can be enhance in the presence of individual characteristics ( Luo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to Smedlund [108], reciprocal benefits enhance information sharing among community members by assuring knowledge owners that their efforts will be compensated in the future. Individuals who hold a more favorable attitude toward reciprocity are usually more likely to respond to beneficial treatment in a back-and-forth manner by providing benefits to other members in exchange for the reward [106,109]. These individuals generally believe that human beings are benevolent and trustworthy, and, as a result, they have a longer-term perspective on gains [110].…”
Section: The Moderating Role Of Reciprocity and Trustmentioning
confidence: 99%